2004
DOI: 10.1016/j.jbiomech.2003.12.034
|View full text |Cite
|
Sign up to set email alerts
|

Do microcracks decrease or increase fatigue resistance in cortical bone?

Abstract: Fatigue of cortical bone produces microcracks; it has been hypothesized that these cracks are analogous to those occurring in engineered composite materials and constitute a similar mechanism for fatigue resistance. However, the numbers of these linear microcracks increase substantially with age, suggesting that they contribute to increased fracture incidence among the elderly. To test these opposing hypotheses, we fatigued 20 beams of femoral cortical bone from elderly men and women in load-controlled four po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 32 publications
3
49
2
Order By: Relevance
“…First, generation of new osteons will produce a smaller cutting cone, minimizing the effects of porosity, and thus the overall strength of the intracortical matrix. Second, dense concentrations of smaller osteons will absorb energy more efficiently than larger ones as the effects resulting from accumulated microdamage are reduced, with cement lines serving to limit crack propagation (Sobelman et al, 2004;O'Brien et al, 2005). Third, smaller osteons in regions of high strain may enhance the resistance towards osteon pullout or debonding of the osteon along the cement line surface (Skedros et al, 2007).…”
Section: Future Directionsmentioning
confidence: 99%
“…First, generation of new osteons will produce a smaller cutting cone, minimizing the effects of porosity, and thus the overall strength of the intracortical matrix. Second, dense concentrations of smaller osteons will absorb energy more efficiently than larger ones as the effects resulting from accumulated microdamage are reduced, with cement lines serving to limit crack propagation (Sobelman et al, 2004;O'Brien et al, 2005). Third, smaller osteons in regions of high strain may enhance the resistance towards osteon pullout or debonding of the osteon along the cement line surface (Skedros et al, 2007).…”
Section: Future Directionsmentioning
confidence: 99%
“…It has been proposed that a microstructural barrier concept may exist in bone (Martin and Burr [11], Taylor and Prendergast [12], Akkus and Rimnac [13]; Sobelman et al [14]) whereby the microstructure of osteonal bone provides barriers to crack growth in the form of cement lines which surround secondary osteons. The cement line interface between osteons and interstitial bone is relatively weak which means that it may reduce the shear strength of osteonal bone (Frasca [15]).…”
Section: Introductionmentioning
confidence: 99%
“…The possibility that CFO and/or other aspects of collagen content/structure are mechanically adaptive in this context is supported by results of past investigations (Burstein et al, 1975;Shelton et al, 2000;Wang et al, 2001;Zioupos et al, 1999). For example, in human bone, Wang et al showed that the percentage of denatured collagen compared to the total collagen content is significantly related to failure energy and fracture toughness (work), supporting the idea that collagen in bone is a primary arrestor of microcracks (Burr, 2002;Sobelman et al, 2004).…”
Section: High Elastic Moduli In Tension: Adaptation or Inherentmentioning
confidence: 81%